2009
DOI: 10.1038/leu.2009.77
|View full text |Cite|
|
Sign up to set email alerts
|

CMC-544 (inotuzumab ozogamicin), an anti-CD22 immuno-conjugate of calicheamicin, alters the levels of target molecules of malignant B-cells

Abstract: We studied the effect of CMC-544, the calicheamicin-conjugated anti-CD22 monoclonal antibody, used alone and in combination with rituximab, analyzing the quantitative alteration of target molecules, that is, CD20, CD22, CD55 and CD59, in Daudi and Raji cells as well as in cells obtained from patients with B-cell malignancies (BCM). Antibody inducing direct antiproliferative and apoptotic effect, complement-dependent cytotoxicity (CDC) and antibody-dependent cellular cytotoxicity (ADCC) were tested separately. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Our in vitro study suggested that the combination use of GO and MDR modifiers may be an ideal therapeutic approach for P-gp-expressing leukemia cells, assuming that the hematologic and non-hematologic toxicities are not worsened. Interestingly, similar results were obtained in studies using inotuzumab ozogamicin, a calicheamicinconjugated anti-CD22 antibody, for lymphoid malignancies [53,54].…”
Section: Drug Resistancesupporting
confidence: 66%
“…Our in vitro study suggested that the combination use of GO and MDR modifiers may be an ideal therapeutic approach for P-gp-expressing leukemia cells, assuming that the hematologic and non-hematologic toxicities are not worsened. Interestingly, similar results were obtained in studies using inotuzumab ozogamicin, a calicheamicinconjugated anti-CD22 antibody, for lymphoid malignancies [53,54].…”
Section: Drug Resistancesupporting
confidence: 66%
“…The toxin or drug moieties of these biotherapeutic agents are delivered into target leukemia cells together with the targeted CD22 molecules by antibody-mediated endocytosis (56)(57)(58)(59). Antibody-mediated internalization of CD22 is dependent on its physical interaction with the clathrin-associated AP-2 adapter complex via tyrosinebased specific internalization motifs within its cytoplasmic domain (59,60).…”
Section: Resultsmentioning
confidence: 99%
“…When administered to xenograft models, CMC-544 prevents engraftment, but also induces dose-dependent tumor regression in mice presenting with leukemia. Whereas the level of CD22 expression is significantly reduced after incubation with CMC-544, the CD20 level can be increased (Takeshita et al, 2009). Therefore, sequential administration of rituximab increases the cytotoxic effect and supports the rationale for a combination with other antibodies.…”
Section: Cd22 Immunoconjugatesmentioning
confidence: 87%